The Language of Fashion as a Carrier of Personal Information - Kosowska-Ślusarczyk, Marta (Journal of Education Culture and Society, 2020)
It’s fair to say that all human life is based on communication; passive and active, verbal and nonverbal. No matter which media type you consider, the importance of the so-called first impression cannot be overstated. Currently, as the world becomes more open and accessible, the individual character of the way we create our look takes a different form, but still remains an important messenger. In my thesis, I would like to present the outfit as a carrier of vital information about people. In parallel, I will analyze the clothing itself, researching both historic and contemporary sources. Finally, I attempt to decipher the language of fashion.